[tex]\ln(n+3)-\ln n=\ln\dfrac{n+3}n=\ln\left(1+\dfrac3n\right)[/tex]
We can show the sequence is bounded and monotonic.
Boundedness: [tex]1+\dfrac3n>1[/tex] for all [tex]n>0[/tex], so [tex]\ln\left(1+\dfrac3n\right)>\ln1=0[/tex] for all [tex]n>0[/tex].
Monotonicity: Consider the function
[tex]f(x)=\ln\left(1+\dfrac3x\right)[/tex]
which has derivative
[tex]f'(x)=\dfrac{1+\frac3x}{-\frac3{x^2}}=-\dfrac3{x^2+3x}[/tex]
which has negative sign for all [tex]x>0[/tex], and so [tex]f(x)[/tex] is strictly decreasing.
[tex]\ln(n+3)-\ln n[/tex] is bounded and monotonic, so the sequence converges.
As [tex]n\to\infty[/tex] we have [tex]\dfrac3n\to0[/tex], leaving us with the limit
[tex]\displaystyle\lim_{n\to\infty}(\ln(n+3)-\ln n)=\lim_{n\to\infty}\ln\left(1+\frac3n\right)=\ln\left(1+\lim_{n\to\infty}\frac3n\right)=\ln1=0[/tex]